Propofol-Based Sedation Does Not Increase Rate of Complication during Percutaneous Endoscopic Gastrostomy Procedure - Somchai Amornyotin; Wiyada Chalayonnavin; Siriporn Kongphlay (Gastroenterology Research and Practice)
Objectives. To evaluate and compare the complication rate of sedation with or without propofol regimen for percutaneous endoscopic gastrostomy (PEG) in a hospital in Thailand. Subjects and Methods. A total of 198 patients underwent PEG procedures by using intravenous sedation (IVS) from Siriraj Hospital, Thailand from August 2006 to January 2009. The primary outcome variable was the overall complication rate. The secondary outcome variables were sedation and procedure related complications, and mortality rate. Results. After matching ASA physical status and indications of procedure, there were 92 PEG procedures in propofol based sedation group (A) and 20 PEG procedures in non-propofol based sedation group (B). All sedation was given by residents or anesthetic nurses directly supervised by staff anesthesiologist in the endoscopy room. There were no significant differences in patients' characteristics, sedation time, indication, complications, anesthetic personnel and mortality rate between the two groups. All complications were easily treated, with no adverse sequelae. Mean dose of fentanyl and midazolam in group A was significantly lower than in group B. Conclusion. Propofol-based sedation does not increase rate of complication during PEG procedure. Additionally, IVS of PEG procedure is relatively safe and effective when performed by physicians in training. Serious complications are none.